The minimum means of reprisal : China's search for security in the nuclear age - Lewis, Jeffrey G. (American Academy studies in global security., 2007)
An analysis of China's nuclear and space capabilities, deployment strategies, and stance in arms control negotiations, and the implications for U.S. defense strategy.